2023
DOI: 10.1007/s00381-023-06080-2
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in transitional care to adulthood for patients with cerebral palsy: a systematic review

Abstract: Purpose The transition from pediatric to adult care can be complex and difficult to navigate for adolescents with cerebral palsy (CP). We aimed to assess the current state of transitional care for young persons with CP and delineate guidelines for best practice with opportunities for intervention. Methods A systematic review was conducted using PRISMA guidelines to search PubMed, Embase, and Scopus databases. Articles were screened for relevance via title … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…A systematic review of observational studies showed transition-associated poor outcomes including housing instability, unemployment, difficulty forming relationships, increased hospital admission rates, and decreased use of rehabilitation services. Factors associated with improved outcomes included family participation, promotion of self-efficacy, and meeting the adult team before transition ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review of observational studies showed transition-associated poor outcomes including housing instability, unemployment, difficulty forming relationships, increased hospital admission rates, and decreased use of rehabilitation services. Factors associated with improved outcomes included family participation, promotion of self-efficacy, and meeting the adult team before transition ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by risks of a deterioration of care, the underutilization of services and ultimately poor health outcomes. Gaps in transitional care had been identified and recommendations for best practice were established ( 7 , 8 ). Also, for young patients with widespread chronic diseases, care structures to address the obstacles associated with the transition process were established, e.g., transition programs ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Transitional care inadequacies represent major barriers for CP patients [33]. In such cases with specialized procedures pediatric neurosurgeons need to extend their expertise to the unique requirements of adult patients, ensuring they receive comprehensive and effective care.…”
Section: Gain Of Functionmentioning
confidence: 99%
“…Transition programmes have been described in several paediatric conditions such as transplant surgery 5 or cerebral palsy. 6 These interventions have shown the potential to improve timely access to specialised care and strengthen patient knowledge about their condition. 7 8 Although Mackie et al were able to reduce delays of access to care by 5 months in their transition intervention for paediatric cardiac surgery, there were no differences between the intervention and control group in cardiac re-intervention or readmissions.…”
Section: Introductionmentioning
confidence: 99%